Distal root curvatures in mandibular molars: analysis using digital panoramic X-rays - Fuentes, Ramón; Farfán, Constanza; Astete, Nicolás; Navarro, P.; Arias, Alain
Background: The aim of this study was to describe the degree of curvature in distal roots in the first and second permanent mandibular molars in a Chilean patient sample. A cross-sectional descriptive study was conducted in which digital panoramic X-rays were analysed. Materials and methods: Examinations of patients under 18 years, with signs of distortion or alteration in the contrast or the presence of pathologies that affected visualisation of the roots and pulp-chamber floor of the teeth to be analysed were excluded. Using the AutoCad software, an angle was drawn to represent the curve of the root in its different thirds, drawing lines inside the root canal from the pulp-chamber floor to the dental apex. Using the classic definition of dilaceration (root curvature > 90°), its prevalence was established. 412 teeth and roots were analysed, finding a dilaceration prevalence of 0.73% (n = 3). 84.72% of the roots presented some type of curvature. Results: The middle third had the highest percentage of curvatures and the greatest average of angular curvature, whereas the cervical third was the straightest. No significant differences were found between the degree of curvature and the gender of the subjects, except for the apical third of tooth 3.6. The analysis of curvature by root third offers to the clinician a better perspective of the directional change of the roots and does not limit it to just the presence of curves in the apical third. Conclusions: The report of the angular degree of the curvatures, in addition to the prevalence of dilacerations, informs to the clinicians about the likelihood of finding difficulties when treating root canals. (Folia Morphol 2018; 77, 1: 131–137)